1996
DOI: 10.1073/pnas.93.16.8241
|View full text |Cite
|
Sign up to set email alerts
|

I-TRAF is a novel TRAF-interacting protein that regulates TRAF-mediated signal transduction.

Abstract: Tumor necrosis factor (TNF) receptorassociated factor (TRAF) proteins associate with and transduce signals from TNF receptor 2, CD40, and presumably other members of the TNF receptor superfamily. TRAF2 is required for CD40-and TNF-mediated activation of the transcription factor NF-#cB. Here we describe the isolation and characterization of a novel TRAF-interacting protein, I-TRAF, that binds to the conserved TRAF-C domain of the three known TRAFs. Overexpression of I-TRAF inhibits TRAF2-mediated NF-KB activati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
159
1
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 200 publications
(162 citation statements)
references
References 21 publications
1
159
1
1
Order By: Relevance
“…ORF-K13-induced NF-kB activation was effectively blocked by a dominant-negative mutant of TRAF2 (amino acids 87 ± 501) (Takeuchi et al, 1996) which has been previously shown to block NF-kB induction by several members of the TNFR family ( Figure 3a). Similarly, I-TRAF/Tank, a protein previously shown to bind to the TRAFs (Cheng and Baltimore, 1996;Rothe et al, 1996), could block NFkB induction by ORF-K13 (Figure 3a). Both the above proteins could also block NF-kB induction by Caspase 8 and MRIT (Figure 3a).…”
Section: Mechanism Of Orf-k13-induced Nf-kb Activationmentioning
confidence: 63%
“…ORF-K13-induced NF-kB activation was effectively blocked by a dominant-negative mutant of TRAF2 (amino acids 87 ± 501) (Takeuchi et al, 1996) which has been previously shown to block NF-kB induction by several members of the TNFR family ( Figure 3a). Similarly, I-TRAF/Tank, a protein previously shown to bind to the TRAFs (Cheng and Baltimore, 1996;Rothe et al, 1996), could block NFkB induction by ORF-K13 (Figure 3a). Both the above proteins could also block NF-kB induction by Caspase 8 and MRIT (Figure 3a).…”
Section: Mechanism Of Orf-k13-induced Nf-kb Activationmentioning
confidence: 63%
“…After reaching a maximum ϳ2 h, transcript levels of genes in these clusters dropped dramatically, to a minimum well below the initial expression level. Our data suggest one possible mechanism for this effect; the TRAF inhibitor TANK (Rothe et al, 1996), which was induced by ER stress (see below, Figure 5), could provide negative feedback to TRAF and result in a decreased AP-1 activity.…”
Section: Transcripts Encoding Many Signal Transduction Proteins Incrementioning
confidence: 99%
“…Overexpression of I-TRAF inhibits TRAF2-mediated NF-kB activation as signaled by CD40 and both TNF receptors. Thus, I-TRAF appears to act as a natural inhibitor of TRAF function (Rothe et al, 1996).…”
Section: Tumor Necrosis Factor Receptor-associated Factors (Trafs)mentioning
confidence: 99%